Bibliometric analysis of research trends and emerging insights of osteoarthritis and chondrocyte hypertrophy - Jiajin Fang; Jiajin Fang; Shuai Wang (Frontiers in Surgery)
BackgroundThis study aims to systematically analyze the intersection of OA and chondrocyte hypertrophy using bibliometric methods, providing an quantitative and comprehensive overview of the current research status and emerging trends in this field.MethodsRelevant publications were retrieved from the Web of Science Core Collection database using the search query TS = (“chondrocyte* hypertroph*” OR “hypertrophic chondrocyte*” OR “cartilage hypertroph*”) AND (“osteoarthriti*” OR “OA” OR “degenerative arthritis”). Several bibliometric tools, including Vosviewer, CiteSpace, the R package (bibliometrix), and Excel 2021, were utilized to systematically analyze the publications on the intersection of chondrocyte hypertrophy and OA.ResultsA total of 639 publications, published between 1995 and 2025, were identified. The findings indicate a steady global increase in research on OA and chondrocyte hypertrophy, with an increasing number of studies being published in high-impact journals, suggesting a promising developmental trajectory. China and the United States are leading in this field. OSTEOARTHRITIS AND CARTILAGE is identified as the core journal in this area, while ANNALS OF THE RHEUMATIC DISEASES has the highest impact factor among the top publishing journals. Keyword analysis reveals that research hotspots primarily focus on stem cells, tissue engineering, cartilage repair, inflammation, oxidative stress, autophagy, apoptosis, senescence, and related bioactive factors.ConclusionThis study elucidates the current research status and trends at the intersection of OA and chondrocyte hypertrophy, providing crucial references for future research. Future studies should continue to focus on these potential therapeutic approaches, key phenotypes, and regulatory mechanisms, enhance international cooperation to develop more effective strategies and treatments for OA.